2016
DOI: 10.1136/bmjopen-2014-005148
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fasting glucose is associated with increased severity of subclinical coronary artery disease compared to patients with diabetes and normal fasting glucose: evaluation by coronary computed tomographic angiography

Abstract: ObjectiveThis study was designed to evaluate the severity of subclinical atherosclerosis in patients with asymptomatic impaired fasting glucose (IFG) compared to those with diabetes mellitus (DM) and normal fasting glucose (NFG), as measured by coronary computed tomographic angiography (CCTA).DesignSubjects were divided into three groups: NFG (<100 mg/dL), IFG (100–125 mg/dL) and DM. Coronary artery calcium on non-contrast CT and plaque analysis on CCTA were performed.SettingUniversity hospital, single centre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The DECODE study indicated that abnormal glucose tolerance also increased the risk of cardiovascular disease and led to a poor prognosis [6]. Patients with an impaired fasting glucose (IFG) level and impaired glucose tolerance (IGT) have more severe coronary artery lesions [7]. Hyperglycemia is also an independent risk factor for both in-hospital and long-term poor prognosis in AMI patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…The DECODE study indicated that abnormal glucose tolerance also increased the risk of cardiovascular disease and led to a poor prognosis [6]. Patients with an impaired fasting glucose (IFG) level and impaired glucose tolerance (IGT) have more severe coronary artery lesions [7]. Hyperglycemia is also an independent risk factor for both in-hospital and long-term poor prognosis in AMI patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery lesions can also be detected in the pre-diabetic state, including in patients with impaired fasting glucose (IFG) and impaired glucose tolerance. 2,3 There is thus a need to identify the early signs of atherosclerosis in patients with DM and pre-DM, to allow early interventions to treat the atherosclerotic process.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence from studies employing CCTA assessments indicates that the following are independent risk factors for coronary atherosclerosis: age [36], diabetes mellitus [37], hypertension [38], smoking [39,40], chronic kidney disease [41], hyperlipidemia [42], and familial hypercholesterolemia [43]. One study revealed that no single risk factor incurred a significantly higher risk of significant artery stenosis, with a combination of risk factors being required [44].…”
Section: Discussionmentioning
confidence: 99%